2007
DOI: 10.1111/j.1469-7998.2007.00291.x
|View full text |Cite
|
Sign up to set email alerts
|

Diet of free‐ranging cats and dogs in a suburban and rural environment, south‐eastern Brazil

Abstract: In spite of the worldwide occurrence of domestic cats and dogs, and their close relationship with humans, the number of published papers on free-ranging cats Felis catus and dogs Canis familiaris, is small. The diet of both species was estimated in a suburban and rural environment in July 2002 and January 2003. Visual observations and scat collection of both species were accomplished along a 10 km transect line in the Campus 'Luiz de Queiroz', University of Sa˜o Paulo, Piracicaba, south-eastern Brazil. The die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
0
37

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(124 citation statements)
references
References 17 publications
5
82
0
37
Order By: Relevance
“…Free-ranging dogs often come into contact with wildlife and interact negatively [13,14], sometimes even outcompeting native species [15], as well as posing a high risk of disease spillover to native carnivores, especially to wild canids and felids [5]. Studies from around the globe highlight the influence of free-ranging dogs on native fauna [3,5,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Free-ranging dogs often come into contact with wildlife and interact negatively [13,14], sometimes even outcompeting native species [15], as well as posing a high risk of disease spillover to native carnivores, especially to wild canids and felids [5]. Studies from around the globe highlight the influence of free-ranging dogs on native fauna [3,5,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Dogs, as one of the most widely distributed carnivores, also interact with wildlife in various environments across rural-urban gradients. They often adopt the role of predators [2,3], prey [4][5][6], competitors [7] and reservoirs or transmitters of disease [8,9]. Additionally, they may also take up the role of "conservation dogs" (sensu Reed et al [10]), and are employed in wildlife research and management [11].…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to the high number of feral dogs ranging in the wetlands, cats were rarely seen in the circle sites. Campos et al (2007) compared the distribution and analyzed the diet of feral cats and dogs in Brazil and found that both were more abundant in suburban than in rural areas and their diet consisted mostly of invertebrates, followed by mammals and birds. We have found no other published studies of cat predation on birds in Latin America, but such studies are badly needed.…”
Section: Interactions With Other Speciesmentioning
confidence: 99%
“…thous on PESB. The domestic dog has a negative impact on mammals, being a potential predator, competitor and is also source of several diseases (Butler and du Toit 2002;Butler et al 2004;Curi et al 2006;Galetti and Sazima 2006;Campos et al 2007). In one occasion (August 2006) two dogs killed an adult male capuchin monkey (Sapajus nigritus) on PESB (Oliveira et al 2008), demonstrating the need of urgent management actions.…”
Section: Carnivoramentioning
confidence: 99%